Analisis Dampak Pendapatan Daerah Terhadap Kemiskinan dan Pengangguran dengan Belanja Bantuan Sosial sebagai Pemediasi - Ramadani, Himammul Adhim; Rochmatullah, Mahameru Rosy (Universitas Muhammadiyah Metro, 2024)
The aims of this study are to explore the impact of Local Own-Source Revenue (LOS), General Allocation Fund (GAF), and Special Allocation Fund (SAF) on the levels of poverty and unemployment through the allocation of social assistance spending in various districts/cities in Java Island in 2022. It employs a quantitative approach with path analysis, using a sample of 110 data points. The findings indicate that indirectly, LOS and SAF do not significantly influence the poverty level through the allocation of social assistance spending, whereas GAF has a significant impact on poverty through the mechanism of social assistance spending. Additionally, there is no significant indirect effect of LOS, GAF, and SAF on the unemployment level through the allocation of social assistance spending